Physically based modeling of shear modulus‐temperature relationship for thermosets. Issue 12 (7th October 2015) - Sun, Wei; Vassilopoulos, Anastasios P.; Keller, Thomas
Abstract : A new physically based model for the simulation of the imaginary part of the shear modulus‐temperature ( G ″‐T) curve of thermosets is introduced in this paper. The model is based on the modification of the G ″‐ T equation used for thermoplastic polymers via the introduction of two new formulations regarding the calculation of the configuration probability and the velocity matrix of the examined thermosets. The formulations for the calculation of the probability of configuration and the velocity matrix of the polymer chain were modified according to the cross‐linking structure of thermosets. In addition, an arctangent function is proposed to consider the effect of temperature on the mean square separation of the ends of the sub‐molecules. All the parameters necessary to calibrate the model can be either estimated or experimentally derived using low‐frequency dynamic mechanical analysis. The newly introduced model is based on a sound physical background, and can be used for the investigation of the effect of the molecular structure of thermosets on their loss modulus and their glass transition temperature. POLYM. ENG. SCI., 55:2893–2898, 2015. © 2015 Society of Plastics Engineers